(3GdGSJYGfI HGdPcGA GdGUWfGYj aj JfajP YbhHI GdeQGbHI GdEdcJQhfjI (B:s (3OQGSI JMdjdjI ebGQfI (B/s - (3EHQGgje, eMeO LHQjds ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2024)
(3cJGH (B"(3GdGSJYGfI HGdPcGA GdGUWfGYj aj JfajP YbhHI GdeQGbHI GdEdcJQhfjI (B: (3OQGSI JMdjdjI ebGQfI(B" (3ddeSJTGQ GdOcJhQ eMeO LHQjd EHQGgje jJfGhd cjajI GSJNOGe GdPcGA GdGUWfGYj aj JfajP YbhHI GdeQGbHI GdEdcJQhfjI(B. (3jZWj GdcJGH eLehYI ef GdehVhYGJ GdegeI, efgG eaghe GdeQGbHI GdEdcJQhfjI hCSSgG heG jTGHggG ef CfXeI YbGHjI HOjdI, GdYfGUQ GdafjI hGdeGOjI ddeQGbHI GdEdcJQhfjI, hGdWHjYI GdbGfhfjI dgG(B. (3ceG jfGbT GdcJGH GdeQGbHI GdEdcJQhfjI cfXGe MOjK ddeYGedI GdYbGHjI, hjSJYQV GdGNJdGa Hjf fXGe GdeQGbHI GdEdcJQhfjI hhba JfajP GdYbhHI(B. (3jJfGhd GdcJGH CjVG GdfXGe GdbGfhfj ddeQGbHI GdEdcJQhfjI, GdELQGAGJ GdbGfhfjI dJWHjbgG, hGdCKQ GdeJQJH Ydi GdMce HgG, HGdEVGaI Edi ehVhYGJ CNQi PGJ UdI(B. (3jbOe GdcJGH JMdjdG TGedG dcjajI JWHjb gPg GdJbfjI GdMOjKI aj GdfXGe GdYbGHj, eY GdJQcjR Ydi GdLhGfH GdbGfhfjI hGdafjI(B. s
(3HHdjhLQGajI (B: (3UaMI (B145-147.s
Keywords: (3GdeQGbHI GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs; (3GdPcGA GdGUWfGYjs -- (3bhGfjf hJTQjYGJs; (3GdLQGFe GdMGShHjIs -- (3bhGfjf hJTQjYGJs